Perennial grass ley rotations with annual crops in tropical Africa: a review - Wortmann, Charles S.; Bilgo, A.; Kaizzi, C.K.; Liben, F.; Garba, M.; Maman, N.; Serme, I.; Stewart, Z.P. (Wiley, 2021)
Rotation of grass ley with periods of annual crop production can be a means to increased farming system productivity, sustainability, and profitability. This research review offers interpretations of rotation research results for future African agriculture. Some rotation studies were with naturally generated and severely over-grazed fallows consisting primarily of annual plant species but other studies were with planted and well-managed perennial grass ley. Generally, the rotations increased annual crop yields with soil improvement. System benefits were similar or greater for ley compared with fallow with generally higher fodder yields with ley. Surface crusting of sandy soil in the Sahel is a major concern that may be worsened by fallow due to the deposition of clay and silt particles. Ley and fallow were terminated in all studies with inversion plow tillage with more tillage for subsequent crops while the rotation benefits may be greater with less tillage. Most studies did not have fertilizer use but annual crop yield response to fertilizer was greatly increased following ley in one study and with no system by fertilizer interaction effect in three studies. The profitability of ley rotations will vary with fodder demand which is rapidly increasing, especially near urban areas. Strip cropping, for example, alternate ley with annual crop strips of 5–20 m width and rotation cycles of 6–10 yr, may often be optimal for erosion control and sediment trapping, protection from uncontrolled grazing, and nearby supply of vegetative planting material for ley re-establishment. Rotation management can be improved through experiential learning and experimentation.